MENINGKATKAN KREATIVITAS MELALUI KERAJINAN TANGAN MENJADI PRODUK DECOUPAGE BERSAMA MASYARAKAT DESA MEDALKRISNA - Lestari, Asti; Arrahim, Arrahim; Al Ramadhan, Muhammad Fakhran (An-Nizam, 2024)
This community service activity takes the form of training in decoupage crafts from used materials which is carried out in accordance with the conditions of the community, especially housewives who are considered less productive in using their free time. Handicrafts in Medalkrisna Village are less effective, resulting in low community motivation, including in basic literacy activities. To overcome this training on crafts to become decoupage products was carried out for mothers to help increase the creativity of mothers who were also expected to be able to create products of superior quality and utilize used goods which were expected to increase household income. Crafts themselves are artistic activities that involve changing raw materials found in the local environment into valuable objects. The method for implementing this KKN activity is readiness stage, socialization program, submission of materials, carrying out creation training (decoupage craft), monitoring and evaluation activities. As long as it is thorough, precise and neat, it will look attractive and have high selling and aesthetic value. This can be seen from the community's enthusiasm for handicrafts during the program activities as well as the increase in community knowledge and skills in making decoupage crafts.